Sync and Swim: The Impact of Medication Consolidation on Adherence in Medicaid Patients. (October 2013) - Ross, Alexander; Jami, Humaira; Young, Heather A.; Katz, Richard
Background: Medication nonadherence is associated with higher cost of care and poor outcomes. Medication refill consolidation (synchronization of refill dates for patients on multiple drugs) is an important component of regimen complexity. We presumed that Medicaid patients with a 30-day medication supply limit would have significant difficulty with refill consolidation. We evaluated regimen complexity and refill consolidation in relation to medication adherence in the Medicaid population.Methods: A survey was administered to 50 Medicaid patients taking 2 or more daily medications in the outpatient setting. The survey included demographics, 13 items related to medication and pharmacy history, and 10 items related to medication regimen complexity and refill consolidation. Chi-square analysis was used to assess the relationship between adherence and missed medication doses due to regimen complexity. Wilcoxon rank sum test was used to determine association between total number of prescribing providers and number of daily medications with various aspects of regimen complexity.Results: 52% were required to go to the pharmacy more than once per month to keep all of their medications filled and 46% missed a day or more of medication because their medications must be refilled on different dates. Those who missed a day or more of medication because of need to refill prescriptions on different days had higher number of prescriptions ( P = .03) and higher number of prescribers ( P = .03).Conclusion: Medicaid patients had low medication adherence in the context of high regimen complexity and poor refill consolidation. This population would benefit from interventions focused on improving synchronization of medication refills.